Eﬀects of diﬀerent types of statins on lipid proﬁle: a perspective on Asians - Meor Anuar Shuhaili, Meor Fairuz Rizal; Samsudin, Intan Nureslyna; Stanslas, Johnson; Hasan, Shariful; Chellappah Thambiah, Subashini (Kowsar Publishing Corporation, 2017)
Context: The present review aimed at reviewing the eﬀects of diﬀerent statins on lipid proﬁle, particularly in Asians. Evidence Acquisition: PubMed searches were conducted using the keywords ‘statin, eﬀect, and lipid proﬁle’ from database inception through March 2016. In this review, 718 articles were retrieved from the primary search. After reviewing the titles, abstracts, and full texts, we found that 59 studies met our inclusion criteria. These also included subsequent reference searches of retrieved articles. Results: CURVES study compared the eﬀect on lipid proﬁle between atorvastatin and other statins. This study demonstrated that low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), and triglycerides (TG) were reduced more with atorvastatin compared to simvastatin, pravastatin, lovastatin, and ﬂuvastatin. However, simvastatin provided a greater elevation of high-density lipoprotein cholesterol (HDL-C) compared to atorvastatin. The STELLAR trial was based on dose-to-dose comparisons between atorvastatin and rosuvastatin eﬃcacy in reducing LDL-C. Te present study also revealed that as the doses of rosuvastatin, simvastatin, and pravastatin increased, HDL-C also increased, with rosuvastatin having the greatest eﬀect. However, HDL-C levels decreased as the dose of atorvastatin increased. The DISCOVERY study involving the Asian population revealed that the percentage of patients achieving the European goals for LDL-C and TC at 12 weeks was higher in rosuvastatin group compared to atorvastatin group. Conclusions: The eﬀects of statins on lipid proﬁle are dose dependent. Most studies showed that rosuvastatin has the best eﬀect on lipid proﬁle. Prescribing lower doses of statins in Asians seems necessary.